Modelling and simulation of energy-saving potential of Sequential Batch Reactor (SBR) in the abatement of ammoniacal-nitrogen and organics - Ismail, Nur Faizah; Jami, Mohammed Saedi; Amosa, Mutiu K.; Muyibi, Suleyman Aremu (Journal of Pure and Applied Microbiology, 2014)
The ammonical nitrogen removal in discharged effluents from a typical sewerage treatment plant has not been consistent with the stringent discharge standards. There is the need to optimize the energy consumption as well as improve the ammonical nitrogen removal in the treatment plant. This study reports the investigation of the behaviour of process dynamicity of ammoniacalnitrogen (NH3-N) removal in a Sequencing Batch Reactor (SBR) through Activated Sludge Model No.1 (ASM1) and standard SBR design computation for optimal aeration time, while meeting the treatment requirements. Thestudy further evaluates the performance of NH3-N removal based on the data obtained from an existing SBR system. The time profile of process dynamics and the minimum required aeration time with maximum nitrogen removal was studied while taking into account the system’s energy consumption. Moreover, the simulation results by MATLAB Software suggested that the process dynamicity of the carbon and NH3-N concentration is 7 hour batch time with one fill and 1.5 hours aeration time. For computation of SBR standard design, the reduction from current 1.5 hours to 1.35 hours of aeration for 80% to 93% of NH3-N removal brought about the total energy saving of up to 10 percent.